Earnings Management in IPO Bound Firms: Evidence From Indian SME Exchanges - Ghalke, Avinash; Chakravorty, Chhatradhari; Rao, S.V D Nageswara (Asian Economic and Financial Review, 2018)
We study earnings management in IPO-bound SME firms that are raising equity capital on the SME exchanges in India. SME exchanges in India are recently incorporated, privately regulated, and have restricted market participation. Managerial decisions such as earnings management influence a firm’s stock performance. In an emerging economy like India with underdeveloped financial markets for SMEs, earnings management also impacts the long-term sustainability of a nascent financing market at an early stage of its development. We find IPO-bound firms on the SME exchanges resort to a higher degree of earnings management vis-à-vis the Main Board IPO-bound firms. The earnings management in SME firms has a negative impact on their stock performance after listing. The evidence of an adverse relationship with the stock performance suggests that earnings management reduces investors’ protection. The reduction in investors’ protection may act as a challenge to the sustainable development of SME exchanges to meet financing needs of the SME sector in India and its emergence as a credible alternative to bank financing.